2017
DOI: 10.3892/ol.2017.6089
|View full text |Cite
|
Sign up to set email alerts
|

Advances in recurrence and malignant transformation of sinonasal inverted papillomas

Abstract: Abstract. Sinonasal inverted papilloma (SIP) is a benign tumor of the nasal cavity and sinus. SIP is characterized by aggressive malignant transformation and a high rate of recurrence. Inadequate removal of the tumor during surgery is one of the most significant contributors to SIP recurrence. A growing body of evidence suggests that molecular alteration in SIP, including human papilloma virus infections, single nucleotide polymorphisms of key genes, deregulation of signaling pathways and immunological changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 89 publications
0
18
0
1
Order By: Relevance
“…The aetiology of ISPs and OSPs is not fully understood, although several studies have suggested that HPV infection, bacterial infections and tobacco smoking may be risk factors . Moreover, a recent case–control study found a significantly increased risk among subjects previously exposed to organic solvents, welding fumes and nickel compounds, extending previous observations indicating an unusually high proportion of cases in those employed in the steel industry and in manufacturing .…”
Section: Introductionmentioning
confidence: 69%
“…The aetiology of ISPs and OSPs is not fully understood, although several studies have suggested that HPV infection, bacterial infections and tobacco smoking may be risk factors . Moreover, a recent case–control study found a significantly increased risk among subjects previously exposed to organic solvents, welding fumes and nickel compounds, extending previous observations indicating an unusually high proportion of cases in those employed in the steel industry and in manufacturing .…”
Section: Introductionmentioning
confidence: 69%
“…Inverted papillomas (IPs), though being an uncommon benign epithelial neoplasm, have generated considerable interest through literature. This interest is that though they are benign, they are locally aggressive and have a propensity to recur, and are sometimes associated with malignancy [1,2] Recurrent disease and metachronous carcinoma can even develop after a prolonged period of time. The term papilloma means neoplasia with epithelial growth, while the US National Cancer Institute's had defined inverting papilloma as a type of tumor in which surface epithelial cells grow downward into the underlying connective tissue, and thus have been coined the term (inverting = inverted) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging also aids in the determination of tumour margins and attachment sites, and a combination of computed tomography (CT) scan, magnetic resonance imaging (MRI) and positron emission tomography. (PET/CT), could be carried out [16]. The CT scan of the paranasal sinuses and orbits, which is the most preferred radiological imaging, was carried out in the patient.…”
Section: Discussionmentioning
confidence: 99%